Student Team Achievement Division (STAD) as an alternative method of counseling guidance in improving student social interaction - Bariyyah, Khairul (Universitas Negeri Padang, 2019)
Social interaction is a dynamic social relationship that deals with individuals with individuals, groups with groups, as well as group relationships with individuals. Social interaction is important in the teaching and learning process to get information. This Student Team Achievement Division (STAD) is a social based learning in which there are small groups that will train students to interact socially. This study aims to determine the effectiveness of Student team achievement division to improve students' social interaction, this research takes the form of classical guidance using a pre-experimental research design in the form of one group pretest posttest using saturated samples. Findings This study shows social interaction before treatment is an average of 52.5 which is in the moderate category and after getting an average treatment of 65.9 which is in high category and proven by the results of Wilcoxon test shows sig (2-tailed) number 0.012 <0.05 , so that the Student team achievement division is effective to improve students' social interaction. The implication of this research is that the Counseling Guidance teacher is expected to provide guidance and counseling services by using the Student Team Achievement Division to become an alternative service to improve students' social interaction